S. aureus Colonization in Atopic Dermatitis Raises Global Concern: Kolonisasi S. aureus pada Dermatitis Atopik Menimbulkan Kekhawatiran Global - Jaafar Ali Muhammad; Assoc.Prof. Dr. Adawia Fadhil Abbas Alzubaidi; Khaled Al-Hussein Muhammad Idris; Mutaman A. A. Kehail (Academia Open, 2024)
Atopic Dermatitis (AD) is often worsened by Staphylococcus aureus colonization, which compromises the skin barrier and increases inflammation. This study aimed to identify risk factors for S. aureus infection in AD patients. Swabs from 100 AD patients at Baqubah Teaching Hospital, Iraq, were analyzed from October to February 2023. S. aureus was identified in 40% of patients using the Vitek 2 device. Results showed a significant correlation between S. aureus colonization and AD, particularly in younger patients, with the highest infection rates in males over 40. These findings highlight the need for targeted treatments to manage S. aureus in AD, potentially improving patient outcomes. Highlights: High Infection Rates: S. aureus found in 40% of AD patients. Age Correlation: Higher colonization in younger AD patients. Targeted Treatment: Emphasize targeted therapies for managing S. aureus in AD. Keywords: Atopic Dermatitis, Staphylococcus aureus, skin barrier, microbial dysbiosis, infection risk